Analysis of the Effect of Inflation and Assets Under Management on the Performance of Equity Mutual Funds in Indonesia - Ramadhanti, Shafira Tasya; Siswantini, Tri (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The research entitled "Analysis of the Influence of Inflation and Asset Under Management on the Performance of Equity Mutual Funds in Indonesia" can be classified as a quantitative type of research which aims to prove the effect of inflation and asset under management on the performance of equity mutual funds in Indonesia. The object chosen in this study is stock mutual funds using a sample of 82 stock mutual fund products in the 2018-2020 period. The analytical method used is Panel Data Regression Analysis using the Eviews 12 program. The results found from this study are that inflation has a significant effect on the performance of stock mutual funds, while assets under management have no effect on the performance of stock mutual funds.